Determinants of training and its impact on firms' performance: evidence from Malaysia - Zulkifli, Izyani; Duasa, Jarita (University of Lucknow, 2009)
This study attempts a brief discussion on human capital development in Malaysia. Using data from an online survey of companies in Multimedia Super Corridor (MSC) Malaysia, it: (1) compares the quantity and quality of training offered by local and foreign MSC Malaysia status companies, (2) analyses the factors that affect the occurrence and magnitude of training for these companies as a whole, and (3) examines the impact of training on the company performance level. The findings indicate that there is no difference between the quantity of training provided by local and foreign MSC Malaysia status companies, though the latter provide significantly better quality training than their local counterparts. Training is more likely to occur among larger MSC Malaysia status companies, those with lower worker turnover rates, those employing more full-time knowledge workers and those with a formal training policy. The magnitude of training provided is, however, largely determined by the size of the company, a strong internal labour market, greater share of R&D expenditures and the undertaking of training grants. The results also show that the total number of knowledge workers trained does have a positive and significant effect on the company’s performance level.